Development of an efficient regeneration and transformation method for the new potential oilseed crop Lepidium campestre - Ivarson, Emelie (BioMed Central, 2013)
BACKGROUND: Lepidium campestre is an undomesticated oilseed species with a great potential to become a new crop for both food and industrial feedstocks production. Genetic modification is needed for further improving the oil quantity and quality of Lepidium. Studies on in vitro shoot regeneration of Lepidium are very limited and there is no transformation protocol available. RESULTS: We have investigated the effects of different factors, especially the type, concentration and combination of plant growth regulators (PGRs) on in vitro shoot regeneration of Lepidium. The results showed that the 2,4-D treatment was crucial to shoot regeneration from different explants. The duration of 2,4-D exposure between 2-4 days did not show significant difference in shoot regeneration, while the effect of 2,4-D concentration varied greatly depending on the type of explants and cytokinins used, for example, the low concentration of 2,4-D combined with TDZ significantly increased the regeneration frequency of hypocotyls. Cotyledon and hypocotyl explants responded differently to cytokinin, for example, TDZ was more effective than zeatin in promoting shoot regeneration from hypocotyls, but did not affect the regeneration of cotyledons which was more affected by high concentration of zeatin. The results also showed that NAA was not effective for shoot regeneration. Germination in light increased the regeneration frequency compared to that in dark. After optimization of the different conditions, an efficient regeneration protocol was developed with the regeneration efficiency of 92.7%. Using this protocol, the transformation frequency of 6% in average was achieved. The presence of transgenes in the transgenic lines was confirmed by GUS staining, PCR and Southern blot analyses. CONCLUSION: Through systematic investigation of important factors affecting in vitro shoot regeneration, we have developed an efficient regeneration and transformation protocol for the genetic modification of Lepidium campestre. The method may also be applied to the related species.